2023
DOI: 10.1186/s12879-023-08578-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial susceptibility pattern of bacterial uropathogens among adult patients in Madinah, Saudi Arabia

Yahya A. Almutawif,
Hamza M. A. Eid

Abstract: Background Urinary tract infection (UTI) is considered one of the most prevalent infections that may lead to many renal complications. They account for almost 10% of all infections in Saudi Arabia, making them the second most common cause of emergency department admissions. Bacterial pathogens, primarily Escherichia coli, Klebsiella spp., Enterococcus spp., Proteus spp., and Staphylococcus spp. are the most causative agents of UTI. This study aims to evaluate the prevalence and antimicrobial su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In addition, several studies conducted in Yemen supported this data [32][33]. Previous studies have indicated that gramnegative bacteria are responsible for approximately 90% of UTI cases, whereas gram-positive bacteria account for only 10% of cases [34]. Approximately 150 million people worldwide are a icted with urinary tract infections (UTIs), which are among the most widespread microbiological illnesses associated with hospitals and communities [35].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In addition, several studies conducted in Yemen supported this data [32][33]. Previous studies have indicated that gramnegative bacteria are responsible for approximately 90% of UTI cases, whereas gram-positive bacteria account for only 10% of cases [34]. Approximately 150 million people worldwide are a icted with urinary tract infections (UTIs), which are among the most widespread microbiological illnesses associated with hospitals and communities [35].…”
Section: Discussionmentioning
confidence: 84%
“…These data demonstrated that the highest resistance rate of P. aeruginosa isolates was observed for nor oxacin and imipenem, corresponding to 88.46% in each case, and the last administered antibiotics showed moderate resistance. The resistance of P. aeruginosa to imipenem has been observed in more than 60% of similar studies [23,34]. Additionally, P. aeruginosa showed resistance rates of 50%, 63%, and 75% to meropenem, nor oxacin, and o oxacin, respectively [24] Furthermore, the highest resistance rate of the Enterobacter sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 However, a study conducted in Madinah, Saudi Arabia, revealed that the most sensitive drugs were vancomycin, nitroxoline, and trimethoprim/sulfamethoxazole, while the most resistant drugs were penicillin and ampicillin. 24 This difference might be related to the difference in study patients and geographic region, in addition to the availability of antimicrobial agents tested, given that some drugs, such as vancomycin and gentamycin, were not included in this study because they were tested in less than 20% of GPB.…”
mentioning
confidence: 99%
“…23 Furthermore, a study conducted in Madinah, Saudi Arabia, showed that the percentage of female patients 52.1% was slightly higher than that of male patients 47.9%. 24 It is commonly recognized that women are more likely to develop UTIs because of the anatomical and physiological features of the urinary tract. 25 In our study, there was a progressive increase in the incidence of positive urine culture with female age during the entire study period.…”
mentioning
confidence: 99%